Maternal effects, reciprocal differences and combining ability study for yield and its component traits in maize (Zea mays L.) through modified diallel analysis - Bonipas Antony John; Kachapur, Rajashekhar Mahantaswami; Naidu, Gopalakrishna; Talekar, Sidramappa Channappa; Rashid, Zerka; Vivek, Bindiganavile; Patne, Nagesh; Shiddappa Ramappa Salakinkop; Prema Gu (PeerJ Inc., 2024)
Combining ability status of the inbred lines is crucial information for hybrid breeding program. Diallel or line x tester mating designs are frequently used to evaluate the combining ability. In the current study a modified diallel model was used, wherein the Griffing's combining ability effects were further partitioned to understand the effects due to maternal and reciprocal. To do this, eight parental lines of maize were crossed in full diallel method and the generated hybrids along with parents were phenotyped. The field data on the quantitative traits was analyzed using both Griffing's and the modified model to determine how well the parents' and the F 1 hybrids combined. For each of the traits, a sizable reciprocal and maternal variance was observed. The number of kernel rows per cob variable had a ratio of additive variance to dominance variance greater than one. All other traits including grain yield had a ratio close to zero, suggesting that non -additive gene action was primarily responsible for the genetic control of most of the traits. The narrow sense heritability was low to moderate for majority of the variables, except for number of kernel rows per cob. With the help of the improved model, it was possible to choose superior parents and cross -parent pairings with accuracy. Based on the modified general combining ability effects and maternal effects, the parental line P5 was recognized as a potential female parent and P7 as a good male parent for grain yield and yield -attributing characteristics. The cross combination of P8 x P1 had the highest specific combining ability effect on grain yield. P5 x P6 cross had the highest reciprocal effect. The correlation analysis implies that the Griffing's general combining ability effects and specific combining ability effects were found to be less efficient in predicting F 1 performance as compared to the modified model.